2021
DOI: 10.1039/d1cc01186c
|View full text |Cite
|
Sign up to set email alerts
|

Anion–π interaction at the solid/water interfaces

Abstract: Anion–π interaction has been found to play a kye role in interfacial phenomena. In this study, we evaluated the anion–π interactions at the solid/water interface. Anion adsorption originating from anion–π...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Figure b shows the plots of E s against the hydration energy (Δ G hyd ) of a series of anions. The anions with lower hydration energies (e.g., F – , SO 4 2– ) afford a more stabilized complex, which corresponds to the trend of anion transport or adsorption because Δ G hyd is related to the electron density of the anions. , In contrast, E s for SO 4 2– , assuming 1:1 stoichiometry, deviated from this trend (black plot in Figure b). The energy trend was reproduced, however, when assuming that SO 4 2– forms a complex with NDI at a 2:1 ratio (red plot in Figure b).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure b shows the plots of E s against the hydration energy (Δ G hyd ) of a series of anions. The anions with lower hydration energies (e.g., F – , SO 4 2– ) afford a more stabilized complex, which corresponds to the trend of anion transport or adsorption because Δ G hyd is related to the electron density of the anions. , In contrast, E s for SO 4 2– , assuming 1:1 stoichiometry, deviated from this trend (black plot in Figure b). The energy trend was reproduced, however, when assuming that SO 4 2– forms a complex with NDI at a 2:1 ratio (red plot in Figure b).…”
Section: Resultsmentioning
confidence: 94%
“…Matile et al developed artificial anion transporters through lipid bilayers based on anion−π interactions using NDI derivatives and systematically investigated the selectivity and cooperative channeling behaviors of the anions . Our group characterized anion−π interactions at the solid/water interfaces using films based on NDI derivatives and revealed the single-molecule force of the anion−π interaction between a negative charge and an NDI unit . Wang reported that anion−π interactions controlled the self-assembly of tetraoxacalix[2]­arene[2]­triazine derivatives with anionic surfactants and the release of incorporated model drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Akamatzu et al prepared a surface modified with an electron-deficient aromatic molecule naphthalenediimide (NDI) and examined its interactions with a negatively charged AFM probe. 202 As illustrated in Figure 10d, in pure water, only repulsive forces were detected on the substrate modified with hydrophilic triethylene glycol (TEG) groups, while the surface functionalized with NDI molecules exhibited an attraction of ∼0.1 nN at a separation of 3−4 nm, owning to anion−π interactions. The introduction of halide anions could suppress the attraction to some extent because of the competing effect, with an inhibition trend of Cl − > Br − > I − .…”
Section: Anion−π Interactionsmentioning
confidence: 99%
“…Compared to poly­(pyrocatechol) coatings that only allowed the formation of cation−π pairs, the bridging effect of anion−π interactions in poly­(PO 4 -DHB) coating resulted in its strong adhesion with cation concentration insensitivity (Figure c), postulated to contribute to wet adhesion of marine organisms. Akamatzu et al prepared a surface modified with an electron-deficient aromatic molecule naphthalenediimide (NDI) and examined its interactions with a negatively charged AFM probe . As illustrated in Figure d, in pure water, only repulsive forces were detected on the substrate modified with hydrophilic triethylene glycol (TEG) groups, while the surface functionalized with NDI molecules exhibited an attraction of ∼0.1 nN at a separation of 3–4 nm, owning to anion−π interactions.…”
Section: Nanomechanics Of Noncovalent Interactions In Polymeric Systemsmentioning
confidence: 99%
See 1 more Smart Citation